Misplace Otoritas Berbagi Konten Keagamaan pada Grup WhatsApp - Siska Nur Apriyani; Ryo Yudowirawan; Fathurozi Fathurozi; Moch Lukluil Maknun; Umi Muzayanah (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Online media undermines the authority of religious preachers because many online media users feel obligated to do da'wah (preaching) even though they do not have the capacity for religious knowledge. Online media provides easy facilities for sharing with many people and groups with one click. The distribution of this religious content such as writing, images or videos is done on various online media platforms including the WhatsApp group (WAG) often without considering the suitability of the content being shared, the audience or WAG members, and the purpose of establishing a WAG. This study intends to reveal the practice of sharing religious content in WAG. This study used a quantitative approach, i.e. the poll method conducted on res- respondents with the criteria of having a religious background, namely employees of the Ministry of Religion and students or alumni of Islamic religious colleges (PTAI) in Semarang City and its surroundings. The re- results of this study show that the religious contents (56.6%) mostly shared on WAG are related to the Koran and hadith. The groups that share the most religious content are organizational groups (54.2%) and family groups (41.6%). Respondents also assess that more than half (51.2%) of the distributors of this material in their WAG do not match their competence in the field of religion. In addition, the distribution of religious content in WAG neither includes authors (creators), namely 63.3%, nor includes references, namely 60.2%. This finding shows that there is a phenomenon of misplaced da'wah in the WhatsApp group, which indicates a deviation in the principle of preaching.